1984
DOI: 10.1139/f84-131
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate of Fishes in the Pelagic Ecosystem

Abstract: A size-dependent equation for mortality rate (M(w)) of fish-sized particles is derived using preexisting theory on the distribution of biomass as a function of size (w) in the pelagic marine ecosystem, assuming that mortality is primarily due to predation. The equation M(w) = ckw−x (where c, k, and x are parameters) yields estimates that are close to observed mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
378
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(392 citation statements)
references
References 0 publications
11
378
2
1
Order By: Relevance
“…Age-independent mortality estimates were almost identical for males and females. Age-specific mortality estimates from the Peterson & Wroblewski (1984) method declined from 0.21 yr -1 for newborn individuals to 0.09 yr -1 at maximum age (32 yr), overlapping the range identified by the age-independent methods.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Age-independent mortality estimates were almost identical for males and females. Age-specific mortality estimates from the Peterson & Wroblewski (1984) method declined from 0.21 yr -1 for newborn individuals to 0.09 yr -1 at maximum age (32 yr), overlapping the range identified by the age-independent methods.…”
Section: Resultsmentioning
confidence: 50%
“…Natural mortality was estimated using a range of indirect techniques based on life-history data to provide a comparison with those estimated from telemetry data. Six estimators of constant lifetime mortality (Pauly 1980, Hoenig 1983, Jensen 1996 and one method of age-specific mortality (Peterson & Wroblewski 1984) were used. All life-history data were taken from Wintner et al (2002) and Dudley & Simpfendorfer (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Methods 5 and 6 produced similar ranges of estimates, roughly in the middle of the collective range. Estimates from method 8, based on weight, were similar to those from method 3 and were nearly identical to estimates based on the more theoretical approach of Peterson and Wroblewski (1984). Although we did not include their approach in Table 1, it would add weight to M estimates in the range of 0.5-1.2 per year.…”
Section: Indirect Estimatesmentioning
confidence: 67%
“…This method allows M to vary among individuals; however, we used it with a range of sizes for exploitable blue crabs (.76 mm CW) to produce a range of M estimates in a way similar to the other methods. Peterson and Wroblewski (1984) concluded that mortality due to predation in pelagic marine ecosystems was a power function of body weight. Lorenzen (1996) related estimates of M to wet body weight for a large and diverse data set for fishes of all sizes in natural ecosystems (lakes, rivers, marine systems) and also found that M was a power function of body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the high asset values (e.g. large energy reserves or body size) lead to higher competitive ability, and reduce risks due to predator gape-limits or increased vigor (Mittelbach 1981;Peterson and Wroblewski 1984;Werner and Gilliam 1984;Travis et al 1985; but see Lima 1986). The influence of these feedback systems could differ in strength in different environmental contexts (e.g.…”
Section: Introductionmentioning
confidence: 99%